Solubility Enhancement of Meloxicam by Binary and Ternary Solid Dispersion (Journal of Pharmaceutical Negative Results, 2022)
The purpose of this study was to improve the solubility and dissolution rate of meloxicam (ME), a water-low soluble analgesic., using binary and ternary solid dispersion by solvent evaporation and kneading methods. Two hydrophilic polymers, polyethylene glycol 4000 (PEG 4000) and polyvinyl pyrrolidine K30(PVPK30), were used in the solid dispersion of (ME), in different drug to polymer ratio. The drug content, percentage yield, and X-ray Diffraction (XRD) and FTIR spectroscopy analyses were used to analyze the pure drug (ME) and its solid dispersion with and without various polymers. The findings of this research revealed a decrease in crystallinity and a change in the drug's crystal habit. The prepared solid dispersions' solubility and dissolution rate were compared to those of the untreated medication. The solubility and dissolution profiles of all prepared formulae improved significantly (p0.05). The best results were obtained using a formula made up of PVP K30 and cross carmelose (CC) in a 1:3 drug-to-polymer ratio with a 5% W/W CC content.